An application of the ELECTRE TRI‐C method to characterize government performance in OECD countries. (8th February 2017) - Costa, Ana Sara; Rui Figueira, José; Vieira, Carlos Rodrigues; Vieira, Isabel Viegas
Abstract: In the 2010 Toronto summit, the leaders of the G‐20 countries agreed on the implementation of urgent fiscal consolidation plans, following the expansionary policies adopted to curb the recessionary effects of the financial crisis. Unprecedented cuts in public expenditures have taken place, particularly in the European Union periphery, reviving the discussion on the optimal size of the public sector. Supporters of fiscal restraint defend that bigger governments tend to be more inefficient, its opponents assume that government size determines the effectiveness of its performance. However, the social and economic impacts from contractionary fiscal policies ultimately depend on the level of public sector efficiency. Relatively inefficient governments have more scope to consolidate without compromising social welfare. In this paper, we adopt a multiple decision aiding approach, not previously employed for the assessment of complex macroeconomic performances, and employ the ELECTRE TRI‐C outranking method to categorize OECD countries on a set of criteria representing the quality of their public sectors. We then compare the obtained classifications with the share of each government's expenditures on GDP, to identify distinct levels of efficiency. Our analysis suggests that various countries exhibit a margin for efficiency gains, attenuating the social and economic effects of fiscal consolidation policies.